Parental Satisfaction and Associated Factors Toward Their Child's Anesthesia Service at a Comprehensive Specialized Referral Hospital in Ethiopia, 2021: A Cross-Sectional Study - Admass, Biruk Adie; Hailemariam, Abebaw Shiferaw; Agegnehu, Abatneh Feleke; Getahun, Amare Belete (Frontiers in Pediatrics, 2022)
Background: Parental satisfaction is an important quality indicator of child’s anesthetic care process. Understanding of parent’s opinions and satisfaction about their child’s anesthesia service in the hospital is vital for hospital funding and parent experience. Objective: To determine the level of parental satisfaction and associated factors about child’s anesthesia service Methods: an institutional based cross-sectional study was conducted from March to June, 2021. A structured questionnaire with background characteristics of parents and children was used to collect data. A total of 238 parents were included in the study. Bi-variable and multi-variable logistic regression analyses were used to identify factors associated with parental satisfaction about their child’s anesthesia service. Crude odds ratio and adjusted odds ratio with 95% Confidence Interval were calculated. In multivariable analysis, variables with a p-value of less than 0.05 were considered as statistically significant. Result: The proportion of parental satisfaction towards their child’s anesthesia service was 77.7 % (95% CI; 72.3-82.4%). Non anxious, male, employed and urban resident parents and parents of pre medicated children were associated with high parental satisfaction score. Conclusion and recommendation: The overall parental satisfaction about their child’s anesthesia service was promising. Parents who were non anxious, male, employed, urban resident and parents whose child had received sedative premedication were associated with high scores of parental satisfaction about their child’s anesthesia service. Sufficient and understandable information delivery to parents reduces the preoperative anxiety of families. Provision of comprehensive information about their child’s anesthesia service and psychological or emotional support is necessary to improve their satisfaction.